New multifunctional isolated microinverter with integrated energy storage system for PV applications - Barros, Luís André Magalhães (2020)
This paper proposes a novel multifunctional isolated microinverter which is able to extract the maximum available power from a solar photovoltaic module and inject it into the power grid, while simultaneously charging a battery energy storage system (BESS). The proposed microinverter integrates a novel DC–DC power converter and a conventional DC–AC power converter. The DC–DC power converter is able to send electrical energy to the secondary side of a high-frequency transformer and to the BESS, using only two power switches. Throughout this paper, the converter topology, the operation modes, the control algorithms, and the development of a laboratory prototype of the proposed microinverter are described in detail. Moreover, simulation and experimental results are presented to demonstrate the feasibility of the proposed solution.